INSTAGRAM DAN WHATSAPP MERUPAKAN MEDIA KOMUNIKASI YANG DIGUNAKAN SEBAGAI STRATEGI KOMUNIKASI PEMASARAN DI ERA NEW NORMAL - Anggelina, Bella; Purwanti, Angel (SCIENTIA JOURNAL, 2022)
In the current New Normal Era, marketing communication strategies can be a tool in maintaining the market for a business. Promotions resulting from the mobilization of marketing strategies can be an alternative way to continue to grow, social media is a way of implementing promotions. The formulation of the problem from the research is divided into 2, the first is how the marketing communication strategy is applied by PT Vitka Sehat Utama in the New Normal Era and the second is how the constraints of the implementation of the marketing communication strategy are. The purpose of this study is to find out what marketing communication strategies are applied to PT Vitka Sehat Utama in the New Normal Era. The type of research used in this research is qualitative research. Data collection techniques were carried out by observation, interviews, and documentation. To gain credibility in qualitative research, this study uses the triangulation method by examining the data that has been obtained. The subjects in this study amounted to 3 people (1 Manager and 2 Employees) selected through purposive sampling technique. Marketing communication strategy is one way to show competitive advantage. Marketing communication strategy can be seen as one of the bases for compiling a comprehensive corporate plan. The result of this research is that the marketing communication strategy approach used by PT Vitka Sehat Utama in the New Normal Era focuses on two social media, namely Instagram and WhatsApp, communication that is created verbally by making adjustments through the theory of marketing communication strategy SOSTAC Paul R. Smith which means that marketing communication strategies require a systematic planning in which they can develop plans taking into account objective conditions which furthermore require evaluation of examinations in order to realize a marketing communication strategy effective.